PREVALENCE AND RISK FACTORS OF THE HYPERTENSION OF TRUNYAN VILLAGE, BALI IN 2019 - Made Violin Weda Yani; Ni Nyoman Gita Kharisma Dewi; I Made Putra Swi Antara; I Gede Putu Supadmanaba; Putu Nadira Widyakania; Niluh Dika Jelita; Cokorde Istri Ayu Laksmi Dewi; Ni Luh Ade Utari (The Indonesian Journal of Public Health, 2022)
Introduction: Hypertension is the cause of 7.5 million deaths, equivalent to 12.8% of total deaths based on WHO data. Trunyan Village currently has limited access to health services, low public awareness of maintaining personal health and environmental health, and no descriptive or analytical data discussing hypertension prevalence and risk factors. Methods: Therefore, this study aims to determine hypertension prevalence and risk factors in Trunyan Village, Bangli. This study used a cross-sectional design, with the subject selection method using simple random sampling and blood pressure status as a dependent variable. The interview was conducted on 55 people, which used a questionnaire. Result: Data analyzed used the chi-square test, and the relationship between variables was considered significant with a p-value <0.05. The prevalence of hypertension in Trunyan Village is 52.7%, with female dominance (65.5%) and age ≤50 years (52.7%). There is a significant relationship between hypertension and age (p<0.01; PR=3.50), the habit of consuming sweet foods (p=0.02; PR=0.54), and family history of hypertension (p<0.01; PR=1.91). Conclusion: It can be concluded that hypertension has a significant relationship with risk factors for age, habits of consuming sweets foods, and a family history of hypertension. Further research needs to be carried out with a larger sample size to obtain more representative results. Keywords: Bali, hypertension, prevalence, risk factors, Trunyan village